MARRIAGE PROBLEMS OF INDONESIAN CITIZENS LIVING IN THE NETHERLANDS UNDER THE PERSPECTIVE OF MARRIAGE LAW - Wahab, Abdul Jamil; Fakhruddin, Fakhruddin; Mustolehudin, Mustolehudin (Analisa: Journal of Social Science and Religion, 2018)
The present study described the process and the problems of marriage registration for Indonesian citizens who live in the Netherlands. Through qualitative approach, the study found that the marriage for Indonesian brides and grooms who are Muslim in Den Haag had been recorded by the Embassy of the Republic of Indonesia in the country. The process of delivering marriage service in the Embassy had been simple and easy if the bride and grooms were able to provide the marriage requirements. On the other hand, mixed-marriages were unable to be recorded in the Embassy; however, these mixed-marriages might be recorded in Gemeente or the office of local authority on the country. In addition, the present study also found that several Indonesian citizens in the Netherlands had decided to opt for sirri marriage or religion-based marriage and thus they did not record their marriage in either the Embassy or the Gemeente. The sirri marriage had been selected because the brides and the grooms did not have valid administrative requirements. These brides and grooms usually registered themselves as life partners. Socially, sirri marriage did not have negative impacts because the partners still had social security provided by the government; as a result, civil, social, and economic rights had not been limited. Furthermore, the present study found that the spouses of mixed-marriages in the Netherlands encountered conflict of laws in which the Marriage Law admitted the law of the state in which the marriage had been held but also urged the single-faith marriage. On that basis, the present study would like to recommend reconstruction of marriage law in Indonesia, by recognizing the marriage record that has been legally carried out in other country.